2019
DOI: 10.3390/ijfs7030054
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Financial Literacy: New Evidence from Europe

Abstract: The hypothesis that people with more financial literacy make better financial decisions and show positive financial behaviors is crucial for more than one stakeholder. A weak connection between financial literacy and financial behaviors jeopardizes the opportunity to invest in financial education and to develop a consumer protection framework based on the chance to develop aware and responsible financial consumers. This study uses data from different countries (Germany, France, Italy, Sweden, the UK), using su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 14 publications
1
31
0
2
Order By: Relevance
“…We measured financial literacy using Lusardi and Mitchell’s [ 63 ] methodology, which is simple and widely adopted in the existing literature (e.g., [ 48 , 53 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]). Moreover, Nicolini and Haupt [ 72 ] found that the Lusardi–Mitchell measurement of financial literacy performs well unless financial literacy is used to explain financial behavior. The three questions which we used to measure financial literacy are as follows:…”
Section: Methodsmentioning
confidence: 99%
“…We measured financial literacy using Lusardi and Mitchell’s [ 63 ] methodology, which is simple and widely adopted in the existing literature (e.g., [ 48 , 53 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]). Moreover, Nicolini and Haupt [ 72 ] found that the Lusardi–Mitchell measurement of financial literacy performs well unless financial literacy is used to explain financial behavior. The three questions which we used to measure financial literacy are as follows:…”
Section: Methodsmentioning
confidence: 99%
“…A further two others concerned borrowing (Mortgages, Loans) and the remaining four concerned saving and investment: Investment diversification, Bonds, Stock Investment and Pensions. The 10 topics, all relevant to the financial well‐being of citizens across contemporary market economies, were identified from a literature review (Nicolini, 2019), building on the five questions devised by Lusardi (2011). To ensure that individual items are similarly relevant, questions concerning specific national financial matters and specific financial products were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Our initial pool of 50 items sampling 10 topics was selected with an international population in mind (see Appendix A, and Nicolini, 2019). Our starting point was the “big five” items devised by Lusardi (2011) and her colleagues (Lusardi and Mitchell, 2011a; 2011b; 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations